Study of aerodynamic characteristics of an aircraft during approach to landing in a disturbed atmosphere - Vyshinsky, Victor V.; Chinh, Doan Cong (Vietnam Journal of Mechanics, 2022)
An approximate method is proposed for determining the aerodynamic effect of coherent vortex structures (CVS) of atmospheric turbulence on an aircraft. As a source of the CVS the vortex wind wakes arising when the atmospheric wind flows around the mountain massif of the Son Tra peninsula, located near the Da Nang airport, and the vortex wake behind the Su-27 type aircraft in the landing configuration are considered. Modeling the formation of a vortex structure is carried out by the grid method within the framework of the boundary value problem for the Reynolds-averaged Navier—Stokes equations. The evolution and stochastics of the far wake are modeled in a two-dimensional approximation by discrete Rankine vortices. The assessment of the increment of forces and moments from the effect of the vortex system on the aircraft was carried out within the framework of the panel method. The situation is considered when a light transport aircraft gets into a vortex wake behind an aircraft with a swept wing and a passenger aircraft of the MS-21 type, approaching for landing at the CVS from a mountainous terrain.